Simulation of Liquid Vapor Equilibrium in Batch Distillation Process from Cellulose (Bamboo) - Sari Ni Ketut; Dira Ernawati (Future Science)
Simulation of batch distillation binary systems using matlab programming language, which results in the appearance of the graph using a spreadsheet tool, less effective and efficient, so it is necessary for the visualization of object-oriented programming language, in addition to easy to be developed at a time when that will come, it has other benefits, in a device project software can use a variety of programming language that supports object-oriented programming, such as C#.Net and VB.Net. This research aims to display the batch distillation simulation of visual binary systems using Mat lab programming. Ethanol-water azeotropic binary system examples and Acetone-Butanol, Acetone-Ethanol, Butanol-Ethanol zeotropic binary system examples, simulation of batch distillation with rigorous method using a model Differential-Algebraic-Equations (DAEs), where liquid vapor equilibrium in batch distillation process from cellulose (Bamboo) with Antoine equation. Profile of liquida composition and vapor composition function dimensionless can be displayed directly from the desktop, to have the azeotropic binary system value profile activity coefficient is not equal to one, while the binary system zeotropic approaching one. Profile of liquida composition and vapor composition maximum from binary system azeotropic is 0.98, while for the binary system zeotropic approaching one. Economically using Mat lab language faster, time efficiency and better performance profile.